The role of BRICS in challenging dollar dominance: Prospects of a common currency - Waqeem Akram; Shehar Bano; Zeeshan Ali; Shumaila Akram (Priviet Social Sciences Journal, 2026)
In this paper, the researcher examines how the BRICS can break the global hegemony of the United States Dollar (USD) and the future of establishing a common currency. The paper is concerned with economic and political reasons behind the initiative, the viability of such a project, and its larger implications in the world context. The study applies a qualitative, comparative and analytical design to use secondary materials such as scholarly research, policy documents and foreign financial information. The Eurozone and de-dollarization in Russia and China are also the case studies that may be viewed as providing comparative information. Results indicate that dissatisfaction with dollar hegemony is increasing especially among emerging economies that are considering it as an instrument of vulnerability to external shocks and sanctions. The BRICS members also seek to cut on the use of USD by encouraging the local currencies trade, creating systems of payment and discussing a common currency. Nonetheless, the project has major challenges such as economic heterogeneity, leadership asymmetry, poor institutions, and lack of credibility. This paper concludes that although a BRICS common currency is still a distant dream, current efforts already portend a slow transition to financial multipolarity. This adds to the world discussions of currency power and brings about the possibility of a more pluralistic world monetary system.